2015
DOI: 10.1186/s13071-015-0969-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying avian malaria vectors: sampling methods influence outcomes

Abstract: BackgroundThe role of vectors in the transmission of avian malaria parasites is currently understudied. Many studies that investigate parasite-vector relationships use limited trapping techniques and/or identify potential competent vectors in the field in such ways that cannot distinguish between an infected or infectious vector. Without the use of multiple trapping techniques that address the specific biology of diverse mosquito species, and without looking at the infection status of individual mosquitoes, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
1
34
0
1
Order By: Relevance
“…56 Such studies could examine whether species of mosquito vectors that are known to share Plasmodium infections in nature 57 are equally effective at transmitting these parasites to hosts, and illuminate whether vector community structure can influence seasonal Plasmodium infection dynamics. 58,59 Seasonal variation in temperature may also influence patterns of Plasmodium transmission. The development rate of some Plasmodium parasites in mosquitoes is strongly linked to ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…56 Such studies could examine whether species of mosquito vectors that are known to share Plasmodium infections in nature 57 are equally effective at transmitting these parasites to hosts, and illuminate whether vector community structure can influence seasonal Plasmodium infection dynamics. 58,59 Seasonal variation in temperature may also influence patterns of Plasmodium transmission. The development rate of some Plasmodium parasites in mosquitoes is strongly linked to ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling methods can influence the community of collected mosquitoes and as a result, the prevalence of haemosporidian parasites [5]. Our trap system relied on LED lamps and human presence as baits, which may have attracted mostly anthropophilic mosquitoes, a result supported by the blood meal analysis of our samples.…”
Section: Discussionmentioning
confidence: 99%
“…Vector-parasite compatibility [5] and mosquito feeding patterns [6] also play a role in parasite distribution. Nevertheless, haemosporidian vectors have received less attention than their vertebrate hosts, and this is especially true for tropical latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence studies conducted in 2011 and 2012 showed that China Creek Park harbored a rich diversity of avian Plasmodium species and lineages in birds (Walther et al 2016) and mosquitoes (Carlson et al 2015). However, there was some incongruence between the prevalence of Plasmodium species in resident birds and mosquitoes.…”
Section: Introductionmentioning
confidence: 99%